Cooperativism, entrepreneurship and economic development: a linking theoretical model - Guzmán Alfonso, Carmen; Barroso González, María de la O; Santos Cumplido, Francisco J. (REVESCO. Revista de Estudios Cooperativos, 2016)
Cooperatives, as a kind of firms, are considered by many scholars as an remarkable alternative for overcoming the economic crisis started in 2008. Besides, there are other scholars which pointed out the important role that these firms play in the regional economic development. Nevertheless, when one examines the economic literature on cooperatives, it is detected that this kind of firms is mainly studied starting from the point of view of their own characteristics and particularities of participation and solidarity. In this sense, following a different analysis framework, this article proposes a theoretical model in order to explain the behavior of cooperatives based on the entrepreneurship theory with the aim of increasing the knowledge about this kind of firms and, more specifically, their contribution to regional economic development.
Keywords: cooperatives; entrepreneurship; entreprises; economic development; cooperative essence.